2020
DOI: 10.1186/s13098-020-00550-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes of circulating neuregulin 4 and its relationship with 25-hydroxy vitamin D and other diabetic vascular complications in patients with diabetic peripheral neuropathy

Abstract: Background: Neuregulin 4 (Nrg4) is a novel neurotrophic adipokine associated with the development of diabetic peripheral neuropathy (DPN), however, the pathological mechanism remains poorly understood. The purpose of our study was to investigate the association of circulating Nrg4 with DPN and 25-hydroxy vitamin D [25(OH)D], a multifunctional secosteroid hormone that regulates other neurotrophic factors and adipokines gene expression, and other diabetic vascular complications. Methods: Circulating Nrg4 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
4
0
3
Order By: Relevance
“…Some studies have found that the level of circulating NRG4 in patients with metabolic syndrome is lower than that in the healthy control group, and the concentration of NRG4 is negatively correlated with the risk of developing metabolic syndrome, and NRG4 concentration may be a protective factor [ 33 ]. However, studies have found no correlation between the circulating NRG4 level and the prevalence of diabetic nephropathy and diabetic retinopathy [ 34 ]. In our study, through the analysis of large sample data, it was found that NRG4 was closely related to the incidence of HCY and DN, and the combination of NRG and HCY had excellent predictive efficacy in predicting early DN of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the level of circulating NRG4 in patients with metabolic syndrome is lower than that in the healthy control group, and the concentration of NRG4 is negatively correlated with the risk of developing metabolic syndrome, and NRG4 concentration may be a protective factor [ 33 ]. However, studies have found no correlation between the circulating NRG4 level and the prevalence of diabetic nephropathy and diabetic retinopathy [ 34 ]. In our study, through the analysis of large sample data, it was found that NRG4 was closely related to the incidence of HCY and DN, and the combination of NRG and HCY had excellent predictive efficacy in predicting early DN of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência da NPD varia entre 50-70% em pacientes com diabetes de longa duração, chegando a 8% em pacientes recémdiagnosticados 3,9,11,13-,15,18-23,25,30 . Aproximadamente 20% dos pacientes diabéticos desenvolverão neuropatia clinicamente significativa dentro de 10 anos após o início do diabetes, e esta proporção pode aumentar para 50% após 10 ou 15 anos 23,27 .…”
Section: Discussionunclassified
“… 68 Moreover, circulating levels of Nrg4 are negatively associated with the severity of type 2 diabetic peripheral neuropathy. 69 , 70 However, a human study exhibits an opposite conclusion. In this study, it was found that serum NRG4 level was negatively correlated with insulin sensitivity and positively associated with the level of high-sensitivity C relative protein (hsCRP).…”
Section: Pathological Role Of Nrg4mentioning
confidence: 99%